2016
DOI: 10.1108/srj-08-2014-0110
|View full text |Cite
|
Sign up to set email alerts
|

Socially responsive consumption behaviour – an Indian perspective

Abstract: Purpose – There is a need to promote socially responsible consumption which would accelerate the efforts of economic upliftment and sustainable development initiated by the government and corporates through corporate social responsibility initiatives. This study aims to explore the factors that contribute to socially responsible consumption across demographic factors. Design/methodology/approach – The socially responsible consumption beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 14 publications
8
30
3
Order By: Relevance
“…For example, Parikh and Parikh (2016) estimated that the adoption of energy efficient appliances by Indian households would reduce domestic CO 2 emissions by 40 per cent. Yet an understanding of sustainable consumption in emerging markets is limited, with further research urgently required on how to promote sustainable behaviour among these consumers (Gandhi and Kaushik, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Parikh and Parikh (2016) estimated that the adoption of energy efficient appliances by Indian households would reduce domestic CO 2 emissions by 40 per cent. Yet an understanding of sustainable consumption in emerging markets is limited, with further research urgently required on how to promote sustainable behaviour among these consumers (Gandhi and Kaushik, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Various terms are used in the literature to relate environmentally and socially responsible consumption, including “socially responsive” (Gandhi and Kaushik, 2016), “green” (Narula and Desore, 2016), “pro-ecological” (Fraijo-Sing et al , 2013) and “pro-environmental” (Meyer, 2015). Sustainable consumption is another term often used that is particularly appropriate for energy efficient appliances (Tanner and Kast, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference of social class might vary the motivation of SRC. Previous research noted a positive link between social class and sustainable behavior (Diamantopoulos, Schlegelmilch, Sinkovics, & Bohlen, 2003), while other research reported that income level is negatively associated to SRC (Gandhi & Kaushik, 2016). This shows that income difference is still vague about how to affect SRC.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Middle‐income people are more likely to engage in SRC because they have a more similar feeling to people in need that SRC helps (Gandhi & Kaushik, 2016). In other words, individuals who have lower income tend to perceive more similarity to the targets in SRC.…”
Section: Theoretical Backgroundmentioning
confidence: 99%